Contrasting the Chromosomal Organization of Repetitive DNAs in Two Gryllidae Crickets with Highly Divergent Karyotypes - Palacios-Gimenez, Octavio M. (PLoS One, 2015)
A large percentage of eukaryotic genomes consist of repetitive DNA that plays an important role in the organization, size and evolution. In the case of crickets, chromosomal variability has been found using classical cytogenetics, but almost no information concerning the organization of their repetitive DNAs is available. To better understand the chromosomal organization and diversification of repetitive DNAs in crickets, we studied the chromosomes of two Gryllidae species with highly divergent karyotypes, i.e., 2n(♂) = 29,X0 (Gryllus assimilis) and 2n = 9, neo-X(1)X(2)Y (Eneoptera surinamensis). The analyses were performed using classical cytogenetic techniques, repetitive DNA mapping and genome-size estimation. Conserved characteristics were observed, such as the occurrence of a small number of clusters of rDNAs and U snDNAs, in contrast to the multiple clusters/dispersal of the H3 histone genes. The positions of U2 snDNA and 18S rDNA are also conserved, being intermingled within the largest autosome. The distribution and base-pair composition of the heterochromatin and repetitive DNA pools of these organisms differed, suggesting reorganization. Although the microsatellite arrays had a similar distribution pattern, being dispersed along entire chromosomes, as has been observed in some grasshopper species, a band-like pattern was also observed in the E. surinamensis chromosomes, putatively due to their amplification and clustering. In addition to these differences, the genome of E. surinamensis is approximately 2.5 times larger than that of G. assimilis, which we hypothesize is due to the amplification of repetitive DNAs. Finally, we discuss the possible involvement of repetitive DNAs in the differentiation of the neo-sex chromosomes of E. surinamensis, as has been reported in other eukaryotic groups. This study provided an opportunity to explore the evolutionary dynamics of repetitive DNAs in two non-model species and will contribute to the understanding of chromosomal evolution in a group about which little chromosomal and genomic information is known.